A survey of the venom of the spider Lycosa vittata by biochemical, pharmacological and transcriptomic analyses. (1st December 2015) - Zhang, Fan; Liu, Changjun; Tan, Huaxin; Wang, Hengyun; Jiang, Yinjie; Liang, Songping; Zhang, Fuping; Liu, Zhonghua
Abstract: Lycosa vittata, mainly distributed in the southwest of China, is a medium-sized and venomous spider, whose venom remains unexplored so far. This study aims to present an overview of the venom. It mainly consisted of diverse peptides and exhibited inhibitory effects on voltage-gated ion channels in rat dorsal root ganglia neurons, with a strongest inhibition on tetrodotoxin-sensitive and tetrodotoxin-resistant voltage-gated Na + channels. Interestingly, it exerted cytotoxicity to cancer cells, with approximately 10-fold selectivity on PC-3 over others, implying the existence of selective anti-PC-3 agents in the venom. Moreover, 51 toxin-like peptides were deduced from the venom gland transcriptome. Bioinformatic analyses suggested their structures might have some distinguished properties and their predicted functions were consistent with the venom activities. This study suggests that the venom is an attractive source of neurotoxins with therapeutic significance, and provides references for the structure and function investigation of specific toxins in the future. Highlights: The venom potently inhibits voltage-gated sodium channels in rat DRG neurons. The venom exerts a robust and selective cytotoxicity to prostate cancer cell PC3. 51 toxin-like peptides were deduced from the venom gland transcriptome. The venom is an attractive source of neurotoxins with therapeutic significance.